Candidate SNP-markers altering TBP binding affinity for promoters of the Y-linked genes CDY2A, SHOX, and ZFY are lowering many indexes of reproductive potential in men - M. P. Ponomarenko; E. B. Sharypova; I. A. Drachkova; L. K. Savinkova; I. V. Chadaeva; D. A. Rasskazov; P. M. Ponomarenko; L. V. Osadchuk; A. V. Osadchuk (Вавиловский журнал генетики и селекции)
Reproductive potential is the most important conditional indicator reflecting the ability of individuals in a population to reproduce, survive and develop under optimal environmental conditions. As for humans, the concept of reproductive potential can include the level of the individual’s mental and physical state, which allows them to reproduce healthy offspring when they reach social and physical maturity. Female reproductive potential has been investigated in great detail, whereas the male reproductive potential (MRP) has not received the equal amount of attention as yet. Therefore, here we focused on the human Y chromosome and found candidate single-nucleotide polymorphism (SNP) markers of MRP. With our development named Web-service SNP_TATA_Z-tester, we examined in silico all 35 unannotated SNPs within 70-bp proximal promoters of the three Y-linked genes, CDY2A, SHOX and ZFY, which represent all types of human Y-chromosome genes, namely: unique, pseudo-autosomal, and human X-chromosome gene paralogs, respectively. As a result, we found 11 candidate SNP markers for MRP, which can significantly alter the TATA-binding protein (TBP) binding affinity for promoters of these genes. First of all, we selectively verified in vitro the values of the TBP-promoter affinity under this study, Pearson’s linear correlation between predicted and measured values of which were r = 0.94 (significance p < 0.005). Next, as a discussion, using keyword search tools of the PubMed database, we found clinically proven physiological markers of human pathologies, which correspond to a change in the expression of the genes carrying the candidate SNP markers predicted here. These were markers for spermatogenesis disorders (ZFY: rs1388535808 and rs996955491), for male maturation arrest (CDY2A: rs200670724) as well as for disproportionate short stature at Madelung deformity (e. g., SHOX: rs1452787381) and even for embryogenesis disorders (e. g., SHOX: rs28378830). This indicates a wide range of MRI indicators, alterations in which should be expected in the case of SNPs in the promoters of the human Y-chromosome genes and which can go far beyond changes in male fertility.